Clinical supervision behaviour: what should be the focus? - Abu Kassim , Noor Lide; Abu Kasim, Noor Hayaty (2010)
The quality of dental practitioners depends on the quality of education they receive; one critical aspect in dental education, therefore, is clinical training. In clinical training, supervisors must not only be clinically competent and knowledgeable, they must also possess good teaching and interpersonal skills to provide necessary feedback and guidance. Purpose: This study examines the quality of clinical teaching provided by clinical supervisors at a dental school in Malaysia from the perspective of year 4 and 5 dental students. Method: A questionnaire adopted from Myers (1977) was used to evaluate the clinical teaching behaviors of the clinical supervisors. Dimensions investigated were (i) evaluation of student performance; (ii) learning environment; (iii) concern for student; (iv) knowledge of dentistry; (v) application of knowledge in clinical supervision; and (vi) teaching competency. A total of 160 year 4 and 5 students were surveyed and their responses to the items on the questionnaire were analyzed using Winsteps version 3.64. Results: The results of analysis indicate that clinical supervisors are perceived to be competent in terms of knowledge of dentistry and are able to apply that knowledge in their clinical teaching. However, they are perceived to be unconcerned about their students learning needs and are unable to provide conducive learning environment.